Analysis of the experience of implementing urban redevelopment projects in Russia - E. I. Andrianova; T. A. Gubacheva; A. V. Sapronenko; E. A. Khalimon (E-Management)
The relevance of the study is determined by the identified shortage of the urban environment in Russia, namely those types of buildings that meet modern requirements. In large cities, the only way to change this situation is redevelopment. This article considers options for stimulating the development of urban areas and optimization of their use through redevelopment. The definitions of the concepts of redevelopment, renovation, gentrification, revitalization are delimited. The classification of types of programs according to the level of management is performed. The advantages and disadvantages of the redevelopment process are presented. Based on the analysis of the regulatory and legal framework, the authors revealed that the concept of “redevelopment” is not defined in any way in it. The practical experience of implementing redevelopment projects and programs in Russia, including development projects of the main industrial zones of the city of Moscow, which are inextricably linked with the strategic development of the constituent entities of the Russian Federation and the implementation of national projects, is analysed. Special attention is paid to the redevelopment project management issues, proposals are presented to increase the efficiency of program management based on the Japanese P2M project management standard. At the end of the study, the authors revealed the results achieved in the implementation of redevelopment projects and evaluated their effectiveness in terms of various indicators.